2019
DOI: 10.3399/bjgpopen18x101633
|View full text |Cite
|
Sign up to set email alerts
|

GP attitudes to and expectations for providing personal genomic risk information to the public: a qualitative study

Abstract: BackgroundAs part of a pilot randomised controlled trial examining the impact of personal melanoma genomic risk information on behavioural and psychosocial outcomes, GPs were sent a booklet containing their patient’s genomic risk of melanoma.AimUsing this booklet as an example of genomic risk information that might be offered on a population-level in the future, this study explored GP attitudes towards communicating genomic risk information and resources needed to support this process.Design & settingSemi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 37 publications
(43 reference statements)
1
25
0
Order By: Relevance
“…general practitioners) are also likely to be involved in the potential implementation of PRS, such as in general population‐based screening. Some of our findings are comparable to another study, which found that general practitioners expect that PRS will impact their clinical practice in the future and they require point‐of‐care resources and clinical guidelines regarding PRS 28 . However, further research is still required to assess the learning requirements and attitudes of nongenetic healthcare providers in different contexts.…”
Section: Discussionsupporting
confidence: 82%
“…general practitioners) are also likely to be involved in the potential implementation of PRS, such as in general population‐based screening. Some of our findings are comparable to another study, which found that general practitioners expect that PRS will impact their clinical practice in the future and they require point‐of‐care resources and clinical guidelines regarding PRS 28 . However, further research is still required to assess the learning requirements and attitudes of nongenetic healthcare providers in different contexts.…”
Section: Discussionsupporting
confidence: 82%
“…While we identified several studies that included obstetricians and fetal medicine specialists, there was a notable absence of studies exploring midwives and FPs views, most likely due to the perception of their peripheral role in prenatal diagnosis. However, there is increasing recognition that FPs and midwives must engage with the growing impact of genomics in health care . Coupled with the preliminary evidence from this review that diagnostic uncertainty is viewed as one of the major negative consequences of prenatal testing, further research is needed to inform the implementation of fetal genomics into maternity care.…”
Section: Discussionmentioning
confidence: 97%
“…Outside of the prenatal setting, FPs believe that communicating genomic risk is a responsibility of primary care and recommended a shared decision‐making approach to guide the testing . FPs believe it is important to ensure that patients understand genomic risk and do not experience long‐term adverse psychological responses.…”
Section: Discussionmentioning
confidence: 99%
“…Smit et al . (2019) found that GPs believe that genomic risk may become a responsibility within primary care and they recommended a shared decision making approach to guide the testing process (37). Many adults are living with a rare disease that is not diagnosed in childhood (38).…”
Section: Discussionmentioning
confidence: 99%